Pengembangan Perangkat Lunak V-Apps Sebagai Aplikasi Untuk Menginformasikan Jadwal Damping Mahasiswa Difabel (Studi Kasus Pusat Studi dan Layanan Disabilitas Universitas Brawijaya) - Mohammad Syaifudin Abdullah; Adam Hendra Brata; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Disability Study and Service Center Brawijaya University is an institution that has a function that is as a service center for students with disabilities. One of the services given to students with a disability is to provide assistance during lectures. To inform the schedule is still using the manual way of contacting students or posted on the bulletin board. Therefore, a V-Apps application is created which can inform the damping schedule. Applications can also confirm the presence of a companion and provide a review to the companion who has confirmed the presence. This app is made using Android and the data used is data from schedule scheduling system from PSLD UB. Development using Software Development Life Cycle Software Prototype with two iterations. The first iteration is the result of requirement analysis and the second iteration is the result of user evaluation. With this method, developers and users can interact during the system creation process. An application has been tested using White Box Testing method using Base Path Testing technique for unit test, Black Box Testing method for validation test with 100% success, and usability method to measure application level ease to a user with the result of 86,5 and 84,5 which mean easy for users.